World Englishes in English Language Teaching - Baratta, Alex (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book provides an in-depth exploration of World Englishes and their place in the English as a Foreign Language (EFL) classroom. It opens with a critical assessment of the research to date that includes analysis of competing and complementary terms such as English as an International Language (EIL), Global English, English as a Lingua Franca (ELF) and 'Glocal English'. Here, and throughout the work, the author problematizes the terminologies used to define and describe Englishes, arguing for example for the need to distinguish between Chinglish and China English. The book then turns to an examination of three case study varieties of non-inner circle English: Konglish, Singlish and Indian English; before exploring the results of an original empirical study into language attitudes concerning several varieties of English among language teachers and learners. Finally, sample exercises for the classroom are provided. This book will be of particular interest to language teachers and teacher trainers, and to students and scholars of EFL and applied linguistics more broadly. Alex Baratta is a lecturer at the Manchester Institute of Education, the University of Manchester, UK. His research focuses on the relationship between language and identity in educational contexts, and he is also the author of Accent and Teacher Identity in Britain (2018).